A Study of Cultural Shock in Bharati Mukherjee’s Novels: Exploring Cultural Shock and Adaptability in Bharati Mukherjee's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper tries to capture the main reason, the quintessential concept behind the dilemma of all the heroines of her novels. Bharati Mukherjee is a Third World Feminist writer whose preoccupation is dealing with the problems and issues related to South Asian Women, particularly India, though she claims that her feelings are more like those of the women of North America. She differs from other writers in the way she deals with her heroines (Indian women immigrants), predominantly with their cultural shock that that overthrows them in life directly or indirectly. This is illustrated very clearly by Tara Banerjee in ‘The Tiger’s Daughter’, Dimple in ‘Wife’, Jyoti in ‘Jasmine ‘and Devi in ‘Leave it to me’, three sisters - Padma, Parvathi and Tara in ‘Desirable Daughters’ and Tara in ‘The Tree Bride’. Though the heroines are described as bold and assertive, they do not escape from this particular behavior born of ‘culture shock’. They have the strong potentiality for adaptability they stand on firm ground to change their lives really, if necessary, andor accept the bitter truth of their lives anyhow.